Characteristics and health care utilization of otherwise healthy commercially and Medicaid-insured preterm and full-term infants in the US - McLaurin KK; Wade SW; Kong AM; Diakun D; Olajide IR; Germano J (Dove Medical Press, 2019)
Kimmie K McLaurin,1 Sally W Wade,2 Amanda M Kong,3 David Diakun,3 Ifedapo R Olajide,1 Jane Germano4 1US Medical Affairs, AstraZeneca, Gaithersburg, MD, USA; 2Wade Outcomes Research and Consulting, Salt Lake City, UT, USA; 3IBM Watson Health, Cambridge, MA, USA; 4Department of Pediatrics, MedStar Georgetown University Hospital, Washington, DC, USA Purpose: This study examined health care utilization and costs during the first year of life for preterm and full-term infants in the US. Subjects and methods: Preterm (<37 weeks gestational age [GA]) and full-term infants born 2003 to 2012 without complex medical conditions were identified in the MarketScan® Commercial and Multi-State Medicaid claims databases using ICD-9-CM diagnosis and diagnosis-related grouping codes. Inpatient and outpatient claims from birth through the first year were analyzed for preterm and full-term subgroups. Results were stratified by payer. Results: There were 1,692,935 commercially insured infants (12.5% preterm) and 1,873,324 Medicaid-insured infants (13.9% preterm). The majority (>75%) of preterm infants were admitted to the neonatal intensive care unit during their birth hospitalization. Generally, mean length of stay and costs for birth hospitalizations increased with decreasing GA. The average cost of a birth hospitalization was US $62,931 (SD $134,347) for commercially insured preterm infants and $43,858 (SD $115,412) for Medicaid-insured preterm infants compared to $2,401 (SD $7,399) and $1,894 (SD $5,444) for commercially insured and Medicaid-insured full-term infants, respectively. Post-neonatal hospitalization rates increased as GA decreased (in full-term to <29 weeks GA: commercial =3.3%–19.5%; Medicaid =6.1%–26.2%). Preterm infants had greater average numbers of outpatient office visits and pharmacy claims than full-term infants. Following birth discharge, mean monthly health care costs per infant increased as GA decreased commercial = $334 to $3,126; Medicaid = $205 to $2,473). Conclusion: During the first year of life, post-neonatal hospitalization rates, outpatient office visits, pharmacy claims, and monthly costs increased as GA decreased. Keywords: claims database, premature, birth hospitalization, health care costs